Advanced Nanovehicles-Enabled Delivery Systems of Epigallocatechin Gallate for Cancer Therapy - Li, Kai; Teng, Chao; Min, Qianhao (Frontiers in Chemistry, 2020)
Epigallocatechin gallate (EGCG) is the most abundant polyphenolic constituents derived from green tea extract, which demonstrated to be of versatile bioactivities in combating cardiovascular diseases, neurodegenerative diseases, diabetes and cancer. Particularly, in view of its anticancer activity, increasing attentions have been paid on the developing potent strategies of EGCG involved cancer chemotherapy. However, the poor bioavailability and stability of EGCG limit the effectiveness and practicality in the real biomedical applications. To overcome this drawback, nanotechnology facilitated drug delivery systems have been introduced and intensively explored to enhance the bioavailability and therapeutic efficacy of EGCG in cancer treatment and intervention. This review briefly discusses the anticancer mechanisms of EGCG, and then summarizes recent advances in engineering nanovehicles for encapsulating and delivering EGCG towards cancer therapy. In addition, we also highlight successful integrations of EGCG delivery with other chemotherapy, gene therapy and phototherapy in one nanostructured entity for combination therapy of cancers. In the end, the current challenges and future prospects of the nanovehicles-based transportation systems of EGCG for cancer therapy are also discussed.